An Unusual Case of Resistant Hypokalaemia in a Patient with Large Bowel Obstruction Secondary to Neuroendocrine Carcinoma of the Prostate - Umasankar Mathuram Thiyagarajan; A. Ponnuswamy; A. Bagul; A. Gupta (Case Reports in Surgery)
Neuroendocrine Carcinoma of the Prostate (NECP) is rare and only few cases have been reported, constituting less than 0.5% of prostatic malignancies. We report a rare case of large bowel obstruction from NECP posing a further challenge in management due to resistant hypokalaemia. A 70-year-old man presented with clinical signs of large bowel obstruction who was known to have prostatic carcinoma three years ago, treated initially with hormone therapy then chemoradiation. The blood profile showed a severe hypokalaemia and CT scan revealed liver and lung metastases apart from confirming large bowel obstruction from local invasion of NECP. Severe hypokalaemia was believed to be caused by paraneoplastic syndrome from tumor burden or by recent administration of Etoposide. Intensive potassium correction through a central venous access in maximal doses of 150 mmol/24 hours under cardiac monitoring finally raised serum potassium to 3.8 mmol/L. This safe period allowed us to perform a trephine colostomy at the left iliac fossa. The postoperative period was relatively uneventful. This first case report is presenting a rare cause of large bowel obstruction from a neuroendocrine carcinoma of prostate and highlights the importance of an early, intensive correction of electrolytes in patients with large tumor burden from NECP.